architecturally rational hemostat for rapid stopping of massive bleeding on anticoagulation therapy - Lee, Vivian K.; Lee, Taewoo; Ghosh, Amrit; Saha, Tanmoy; Bais, V. Manish; Bharani, Kala Kumar; Chag, Milan; Parikh, Keyur; Bhatt, Parloop; Namgung, Bumseok; Venkataramanan, Geethapriya; Agrawal, Animesh; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2024)
Hemostatic devices are critical for managing emergent severe bleeding. With the increased use of anticoagulant therapy, there is a need for next- generation hemostats. We rationalized that a hemostat with an architecture designed to increase contact with blood, and engineered from a material that activates a distinct and undrugged coagulation pathway can address the emerging need. Inspired by lung alveolar architecture, here, we describe the engineering of a next- generation single - phase chitosan hemostat with a tortuous spherical microporous design that enables rapid blood absorption and concentrated platelets and fibrin microthrombi in localized regions, a phenomenon less observed with other classical hemostats without structural optimization. The interaction between blood components and the porous hemostat was further amplified based on the charged surface of chitosan. Contrary to the dogma that chitosan does not directly affect physiological clotting mechanism, the hemostat induced coagulation via a direct activation of platelet Toll - like receptor 2. Our engineered porous hemostat effectively stopped the bleeding from murine liver wounds, swine liver and carotid artery injuries, and the human radial artery puncture site within a few minutes with significantly reduced blood loss, even under the anticoagulant treatment. The integration of engineering design principles with an understanding of the molecular mechanisms can lead to hemostats with improved functions to address emerging medical needs.
Keywords: biomaterial; clotting; hemostasis; hemostat; trauma